2017
DOI: 10.1097/scs.0000000000003252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Uniaxial Mechanical Stretch on Wnt/β-Catenin Pathway in Bone Mesenchymal Stem Cells

Abstract: Wnt/β-catenin signal is required in bone formation and remodling, but little is known about whether Wnt/β-catenin signal could promote osteogenic differentiation of rat bone marrow mesenchymal stem cells (BMSCs) after uniaxial mechanical stretch. In this study, rat BMSCs were identified by flow cytometry and used for mechanical stretch. A custom-made uniaxial dynamic stretch apparatus was applied for rat BMSCs stretch. There were 2 groups in the study: the mechanical stretch group and the nonstretch control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Subsequently, through a series of cytoplasmic protein interactions, β-catenin accumulates in the cytoplasm, translocates to the nucleus and functions with transcription factors, TCF and LEF-1, to activate bone-associated target gene transcription. This pathway is referred to as the classical Wnt/β-catenin pathway, and it has an important role in bone formation ( 24 , 25 ). Loss-of-function mutations in Lrp5 resulted in osteoblast dysfunction and subsequent osteoporosis ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, through a series of cytoplasmic protein interactions, β-catenin accumulates in the cytoplasm, translocates to the nucleus and functions with transcription factors, TCF and LEF-1, to activate bone-associated target gene transcription. This pathway is referred to as the classical Wnt/β-catenin pathway, and it has an important role in bone formation ( 24 , 25 ). Loss-of-function mutations in Lrp5 resulted in osteoblast dysfunction and subsequent osteoporosis ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is referred to as the classical Wnt/β-catenin pathway, and it has an important role in bone formation ( 24 , 25 ). Loss-of-function mutations in Lrp5 resulted in osteoblast dysfunction and subsequent osteoporosis ( 25 ). Furthermore, Boyden et al ( 26 ) demonstrated that a mutation at position 171 in the Lrp5 protein led to the total loss of dickkopf Wnt signaling pathway inhibitor 1 antagonism in the Wnt signaling pathway in vitro , which resulted in in bone sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…54 Uniaxial stretch of MSCs upregulated the Wnt/β-Catenin pathway, suggesting that mechanical strain promotes proliferation. 98 However, further work is required to determine the magnitude and mode of strain that supports MSC proliferation. Exploiting mechanical cues to maintain and expand stem cell populations in culture is potentially important for scaling up the production of cells for therapeutic applications such as transplantation.…”
Section: Stem Cells Respond To Forcesmentioning
confidence: 99%
“…Indeed, inhibition of endogenous miR-154-5p using an antisense oligonucleotide significantly promoted osteogenic differentiation [ 66 ]. This may partly explain how mechanical stimulation activates the Wnt/β-catenin signaling pathway and promotes bone formation [ 67 ]. Exposure of PDLSCs to stretching force decreased the expression level of activin receptor type IIB (ACVR2B) via a direct interaction of miR-21 with the 3′-untranslated repeat sequence of ACVR2B mRNA [ 68 ].…”
Section: Mirnas Are Involved In the Mechanical Force Modulated Bone Mmentioning
confidence: 99%